2010
DOI: 10.5187/jast.2010.52.3.205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Protein Level and Phase Feeding Regimen on Growth Performance, Carcass Characteristics and Pork Quality in Growing-finishing Pigs

Abstract: Two experiments were conducted to study the effects of dietary protein level and phase feeding regimens on performance, carcass characteristics and pork quality in growing-finishing pigs. In both experiments, growing pigs (n=90; barrows; Landrace × Yorkshire × Duroc) were allotted to 3 treatments. Each treatment had 3 replicate pens comprising 10 pigs in each. In Exp. 1, pigs (average body weight 25.06±0.57 kg) were fed diets having low (17.50-14.50-12.51%), medium (19.49-17.50-13.87%) or high (22.47-19.49-16.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
3
0
0
Order By: Relevance
“…In phase feeding by protein levels, increasing subdivision of growing-finishing phase did not influence on growth performance. Similar to this observation, some researchers indicated that the number of phases did not have any effect on growth performance of growing ·finishing pigs [ 8 , 24 , 26 ]. Since consumption of protein above requirement led to excreta [ 7 ], pig utilized the constant level of crude protein [ 8 ].…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…In phase feeding by protein levels, increasing subdivision of growing-finishing phase did not influence on growth performance. Similar to this observation, some researchers indicated that the number of phases did not have any effect on growth performance of growing ·finishing pigs [ 8 , 24 , 26 ]. Since consumption of protein above requirement led to excreta [ 7 ], pig utilized the constant level of crude protein [ 8 ].…”
Section: Resultssupporting
confidence: 69%
“…Similar to this observation, some researchers indicated that the number of phases did not have any effect on growth performance of growing ·finishing pigs [ 8 , 24 , 26 ]. Since consumption of protein above requirement led to excreta [ 7 ], pig utilized the constant level of crude protein [ 8 ]. In addition, LP5 group which fed diet contained lower protein also showed similar growth performance with P5 group.…”
Section: Resultssupporting
confidence: 69%
“…Data from both experiments showed that growth performance, carcass traits, and meat quality were not affected by phase feeding programmes indicating that the supply of nutrients from both three-phase feeding programme and two-phase feeding programme were sufficient to meet the genetic potential of pigs. In agreement with our results, Choi et al (2010) who reported that three-or four-phase feeding programmes had no effect on growth performance, carcass characteristics and meat Table 4. Effects of expanded corn-wheat-soybean meal (CSBM)-diets and feeding programme on growth performance in growing-finishing pigs (Exp.…”
Section: Itemssupporting
confidence: 93%